Emerging Trends in VR for Science Education - Pecore, John; Harrison, Chase (Innovations in Science Teacher Education, 2025)
Virtual Reality (VR) transforms science education by providing immersive, interactive environments that enhance student engagement and comprehension of complex concepts. Immersive environments in VR offer cost-effective alternatives to traditional labs, enhance teacher preparation by bridging theoretical knowledge and hands-on experience, and equip educators with innovative instructional strategies. Here, we explore emerging trends in VR applications for science education, emphasizing its integration into preservice teacher preparation and classroom instruction. Drawing from observations at a Florida-based virtual charter school, we examine how VR facilitates experiential learning through tools like 360° models, interactive simulations, and gamified tasks. PSTs observed high levels of student engagement, suggesting VR’s potential to motivate learners across diverse contexts. The article highlights VR’s alignment with constructivist pedagogies, enabling students to actively explore the application of technology during science instruction. The body of research available and our observations underscore the necessity of ongoing technological and curricular advancements to optimize VR's impact on science education. Teaching with VR fosters critical thinking, problem-solving, and engagement in STEM disciplines.